"Contesting the Empire of Habit": Habituation and Liberty in Lockean Education. Issue 3 (15th November 2016) - KOGANZON, RITA
Abstract : Although John Locke's educational curriculum has traditionally been seen to aim at creating free citizens capable of independent thought, the centrality of habituation to his pedagogy has recently raised concerns that the Education is no more than "indoctrination" for compliant subjects. I argue here that by re-examining habituation in light of Locke's epistemology, we find that Locke's education does aim at freedom, but that this freedom requires a strong will and a cultivated skepticism. The habits which Locke asks parents to instill are aimed not at programming specific behavior and opinions, but rather at training children to "cross their desires" to strengthen their wills against the impositions of nature, custom, and fashion, which Locke argues pose an far more serious threat to independent thought than parental discipline. Locke's education aims to cultivate a skeptical mental disposition that permits individuals to resist these other sources of habit and to continually question and revise their own convictions.